Strategi Marketing Public Relations X Motorcycle - Muhammad Nur Ilham; Maya Amalia Oesman Palapah (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. A company really needs the role of Marketing Public Relations to compete with its competitors. One of them is a business company in the field of fashion, namely CV. Bi-Ensi Fashionindo. In introducing one of its brands, namely FMC SpeedSupply, Marketing Public Relations conducted a program by participating in automotive events in the country and abroad. The event organized by FMC SpeedSupply is a national BBQ Ride event. With this event, Public Relations FMC SpeedSupply has a goal, namely to build Brand Awareness in the eyes of consumers. The purpose of this research is to find out how the strategies, barriers and evaluation of Marketing Public Relations through the “BBQ Ride” event conducted by FMC SpeedSupply in building Brand Awareness. The theory used in this study is three ways, namely pull, push, and pass. This research was structured using qualitative methods with a case study. While the data collection techniques were conducted by interview, observation, literature study and documentation. The results of this study found that in organizing the